Zadanie 1 Doprowadź wyrażenia do najprostszej postaci. Podaj konieczne założenie.

^ - do potęgi
* - razy

a. 3x - [5x-(2x-1)]
b. 9m^2-(-1) * [ 7m^2-2m-(m^2-3m)]
c.(2a^2-a+3) * (-4a) + 16a(a^2-0,5)
d. ( 2x^2-5xy+4) * 2xy - 7xy
e. (-10x^3 + 5x^2 - 20x) : (5x)+1
f. (-4x^2 + 12x^3y^2 - 16x^4y^3) : ( -4x^2)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-23T11:43:19+01:00
A)3x - [5x-(2x-1)]=3x-[5x-2x+1]=3x-5x+2x-1=-1
b)9m²-(-1) * [ 7m²-2m-(m²-3m)]=
=9m²+1*[7m²-2m-m²+3m]=
=9m²+1*[6m²+m]=
=9m²+6m²+m=
=15m²+m
c)(2a²-a+3) * (-4a) + 16a(a²-0,5)=
=-8a³+4a²-12a+16a³-8a=
=8a³+4a²-20a
d)( 2x²-5xy+4) * 2xy - 7xy=
=4x³y-10x²y²+8xy-7xy=
=4x³y-10x²y²+xy
e)(-10x³ + 5x² - 20x) : (5x)+1=tego nie potrafie zrobic
f)(-4x² + 12x³y² - 16x⁴y³) : ( -4x²) =
=-4(x²-3x³y²+4x⁴y³)/-4(x²)=
=(x²-3x³y²+4x⁴y³)/x²=
=x²(1-3xy²+4x²y³)/x²=
=1-3xy²+4x²y³





e)(-10x3 +5x2 -20x) :(5x) +1 = -2x2 +x - 4 +1= -2x2+x - 3
c jest zle!